# Pre-calculus.

posted by .

Wesley and Delia are playing a math game. Wesley gives Delia these step to follow.

Step 1: Multiply a number by 6 and then subtract by 4.
Step 2: Divide the result by 2
Step 3: Add 3 to the result from the second step.

If Delia's final answer is 19, What was the original number?

• Pre-calculus. -

suppose you pick x
1: 6x - 4

2: (6x-4)/2 = 3x-2

then 3x-2 = 19
3x = 21
x = 7

Delia picked 7

or you can just do everything with inverse operations on reverse order

last thing she did was divide by 2
so first thing we do is multiply by 2
19x2 = 38
the middle thing she did was subtract 4, so we will add 4
38+4 =42
the first thing she did was to multiply be 6, so the last thing we will do is divide by 6
42รท6 = 7

• Pre-calculus. -

i guess it will help.. thank you :)

## Similar Questions

1. ### algebra

I need a step by step explanation on how to add these two equations 2x+3y=1 5x+3y=16 Subtract the first equation from the second. (Subtract left and right sides separately). This gives you 3x = 15 Then divide both sides by 3. x = 5 …
2. ### Algebra help

f(x)=x^3-4x^2-x+4 How do I find the x-intercept for this?
3. ### CHEM

The decomposition of nitrogen dioxide 2NO2-->2NO+O2 occurs in a two-step sequence at elevated tempatures. the first step lis NO2--> NO+O. predict a possible second step that, when combined with the first step, gives the complete …
4. ### pre algebra

solve the equation step by step.list each step along with the property you used during that step. -5 x 1 x 11 x 4
5. ### ALGEBRA HELP

When solving the equation, what property was used to go from step 3 to step 4?
6. ### Quick math help

In which step below does a mistake first appear in simplifying the expression?
7. ### Algebra 1--Step-by-Step

Can someone show me how to solve these step-by-step?
8. ### Chemistry

In a chain mechanism, a reaction in which two free radicals combine to form a stable molecule would be called the A) initiation step B) termination step C) propagation step D) inhibition step E) branching step
9. ### Math

In which step is the error? Step 1: Let x = 1 and y = 1. Step 2: By substitution xy = y^2. Step 3: Multiplying both sides by -1, -xy= -y^2. Step 4: Adding x^2 to both sides, x^2-xy=x^2-y^2. Step 5: Factoring, x(x-y)=(x+y)(x-y). Step
10. ### aps

There are 26 step on flpor at the time saad comes down two step imad step up one step When will tyey meet at what step?

More Similar Questions

Post a New Question